"The New View of Investment": Comment - Matthews, R. C. O. (Quarterly Journal of Economics, 1964)
Journal Article “The New View of Investment”: Comment Get access R. C. O. Matthews R. C. O. Matthews St. John's College, Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 1, February 1964, Pages 164–172, https://doi.org/10.2307/1880552 Published: 01 February 1964